Implementasi Program Campus Social Responsibility (CSR) pada Masa Pandemi Covid-19 (Studi Pendampingan Anak Rentan Putus Sekolah di Kota Surabaya) - Ridwan, Asrifia; Sholihah, Qomariyatus; Wike, Wike (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2022)
This study aims to identify the implementation of child protection policies during the Covid-19 pandemic through the Campus Social Responsibility (CSR) program imposed on circular letter issued by the Surabaya City Social Service number 460/33250/436.7.7/2020 analyzed based on the theory of implementation of Hogwood & Gunn (1984) and Dye's policy impact theory (2017). The results showed that the implementation of the Campus Social Responsibility program during the Covid-19 pandemic was categorized as an unsuccessful implementation since several requirements for the successful implementation of the program were not fulfilled. The impact of the unsuccessful implementation of the Campus Social Responsibility program leads to the potential rate of school dropout at the SMA/ SMK level in Surabaya is quite high. The minimal contribution from various parties involved in the Campus Social Responsibility program has the consequence that the vulnerable school dropouts cannot be handled properly causing the low quality of Human Resources (HR), increasing number of job seekers, open unemployment, moral degradation, poverty, as well as crime.